Equations for stationary NIRS for Urochloa humidicola - CGIAR Research Program on Livestock (2017)
3 new equations for stationary NIRS, each for one forage quality parameter (IVDM, NDF and ADF) with high resolution, and specific for the screening of U. humidicola genotypes.